Somatosensory-Related Limitations for Bimanual Coordination After Stroke. (July 2013) - Torre, Kjerstin; Hammami, Nadhir; Metrot, Julien; van Dokkum, Liesjet; Coroian, Flavia; Mottet, Denis; Amri, Mohamed; Laffont, Isabelle
Background. Bimanual coordinated movements may be impaired after stroke, so an assessment of causes is necessary to optimize rehabilitation strategies. Objective. We assessed the role of afference-based sources of coordination, including phase entrainment and error correction based on visual and somatosensory feedback. Methods. In all, 10 persons with unilateral chronic stroke and 8 age-matched controls participated in a kinesthetic tracking protocol, in which the hemiparetic upper limb was passively driven by the machine. The task consisted of matching the trajectory of the driven limb as accurately as possible with the freely moving limb in 2 conditions: eyes closed and eyes open. We analyzed the continuous relative phase (CRP), the mean absolute difference between positions (ADP) between the positions of the 2 limbs, and the jerk of the matching limb. Results. Coordination instability (CRP standard deviation) and mean ADP were significantly higher for patients with eyes closed, compared with patients with eyes open, controls with eyes closed, and controls with eyes open. Moreover, the jerk was higher for the nonparetic limb of patients than for the control group. Thus, the nonparetic limb did not produce optimally smooth movements even as the motor-driven paretic limb did. Conclusion. Besides deficits caused by interhemispheric competition and motor execution of the paretic limb, somatosensory feedback is a limiting factor in bimanual coordination after stroke. The findings have clinical implications pertaining to the design and individualization of efficient bimanual movement therapy.